Parental perceptions of the impact of COVID-19 restrictions on family-centred care at a paediatric intensive care unit. (2nd August 2021) - Bannerman, Kieran; Aitken, Lorna; Donnelly, Peter; Kidson, Christopher
Abstract : Background/Aims: Restrictions to clinical practice necessitated by the COVID-19 global pandemic exerted pressures on staff, families and patients within the paediatric intensive care unit of the Royal Hospital for Children in Glasgow. The authors sought to explore parents' experiences during this pandemic. Methods: A single centre study was performed using a questionnaire distributed to parents of patients in the 22-bed paediatric intensive care unit. The key areas targeted were visiting restrictions, ward round changes, facilities closures and the need to wear personal protective equipment. Free text responses were reviewed by two authors independently and common themes identified. Results: The findings offer insight into family perceptions that illustrate the negative repercussions of the restrictions to parents. Understanding on the part of the parents was demonstrated throughout; however, restrictions and pandemic interventions also resulted in isolation, distress, exclusion and anxiety. Conclusions: There are no current studies exploring parental perceptions of COVID-19 interventions within paediatric intensive care units. These findings offer insights that illustrate the unique challenges faced by those who strive to deliver family-centred care, and the additional stress that this can put upon parents. The authors propose adaptive strategies to enhance family-centred care at paediatric intensive care units.